Mating behavior, egg laying, and embryonic development in the South American apple snail Asolene pulchella (Ampullariidae, Caenogastropoda) - Tiecher, María José (2013)
Asolene pulchella is a dioecious freshwater snail from the La Plata basin, belonging to the Ampullariidae family. Our aim was to study the reproductive biology, including mating behavior, egg laying and embryonic development under laboratory conditions. Copulations occurred underwater and lasted 2.66 h on average. The males produce fusiform paraspermatic cells (with seven to nine flagella) in addition to euspermatic cells with a corkscrew head, straight middle piece and long flagellum. Females stored sperm for up to 169 days. The egg masses (containing 98.1 eggs on average) are deposited underwater and are composed of many gelatinous packs of 1-4 eggs; the jelly matrix presented numerous calcite microcrystals. The spheroidal egg capsules measured 2.25 mm and contained a yellowish perivitellus of rubbery consistence. The embryonic development extends for 10.8 days on average. Hatchlings measured 1.4 mm and remained on the egg mass, feeding on the jelly. They look like miniature adults but they only began to feed on senescent plant material in their third week of age and they begin aerial lung respiration after 8-10 weeks. The details of the structure of the egg masses and development constitute a rich source of traits for comparative and taxonomic studies in the Ampullariidae.